2015
DOI: 10.1093/cid/civ027
|View full text |Cite
|
Sign up to set email alerts
|

Clofazimine for the Treatment of Multidrug-Resistant Tuberculosis: Prospective, Multicenter, Randomized Controlled Study in China

Abstract: Using Cfz to treat MDR tuberculosis promotes cavity closure, accelerates sputum culture conversion, and improves treatment success rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 22 publications
3
107
0
4
Order By: Relevance
“…This finding was subsequently confirmed in a larger study in Bangladesh (7), and similar results were also reported from observational studies in Niger and Cameroon (8,9). The specific bactericidal and treatment-shortening activity of clofazimine was experimentally evidenced in mouse models of drug-susceptible (10) and drug-resistant (11) TB as well as clinically evidenced in a controlled clinical trial conducted in China (12). Thus, clofazimine appears to have potential as a repurposed drug for improving, i.e., significantly shortening, the treatment of TB.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…This finding was subsequently confirmed in a larger study in Bangladesh (7), and similar results were also reported from observational studies in Niger and Cameroon (8,9). The specific bactericidal and treatment-shortening activity of clofazimine was experimentally evidenced in mouse models of drug-susceptible (10) and drug-resistant (11) TB as well as clinically evidenced in a controlled clinical trial conducted in China (12). Thus, clofazimine appears to have potential as a repurposed drug for improving, i.e., significantly shortening, the treatment of TB.…”
supporting
confidence: 73%
“…Considering the results from these two studies, it is reasonable to expect a treatment-shortening effect of combining clofazimine with first-line drugs in the treatment of patients with TB if the main pharmacokinetic parameters of clofazimine in the mouse are applicable to humans. The decades of experience utilizing clofazimine for multidrug treatment of leprosy patients at daily doses of 50 to 100 mg demonstrate that clofazimine can be safely administered to humans for long periods of time, with the most common adverse reaction being reversible skin discoloration and ichthyosis (12). Thus, clofazimine is extremely unique in that it is an off-patent, available drug that could immediately be evaluated as a repurposed drug for the treatment of TB, and it seems advisable that the contribution of clofazimine as a first-line drug for the treatment of patients with TB should be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of three randomised controlled trials (RCTs) for clofazimine and linezolid [4345], the evidence used to assess the effects of individual medicines on the outcomes of adult patients on longer MDR-TB regimens originated from observational studies. Meta-analysis were conducted on two datasets: 1) an IPD dataset compiled from studies of 9153 patients treated between the early 1980s and 2009 [41], and 2) a study-level aggregated dataset for over 17 000 MDR-TB and XDR-TB patients in 74 studies published between January 2009 and August 2015 (B astos M, L an Z, M enzies R, personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…Studies were included if they were randomized and controlled and if sputum smear or culture results were reported. Sputum culture status after 8 weeks of treatment was the preferred endpoint because this is the sole TB biomarker meeting the criteria of Chau et al [15] as a “known valid” predictor of relapse [16, 17] and failure [18, 19]. Sputum acid-fast smear conversion was substituted for culture in 3 studies in which culture was not reported.…”
Section: Methodsmentioning
confidence: 99%